The trajectory and determinants of dividends on the Johannesburg stock exchange - Sekgosana, Nomasonto (My University, 2022)
This study examines factors affecting the decisions of firms to pay dividends using non-financial firms listed on the Johannesburg Stock Exchange (JSE). The study uses 1) descriptive statistics to draw trends from the data, 2) logit regression using firm-specific factors as independent variables and a firm's decision to either pay or not pay dividends, 3) and portfolio analysis to check the robustness of the results. There is confirmation that firm-specific factors and propensity can explain the declining number of dividend-paying firms over the sample period. The South African stock market has seen a significant decline in the number of firms paying dividends from 1994 to 2020. Additionally, the pool of JSE firms declined from the late 1990s to the early 2000s. However, the overall number of firms on the JSE has remained stable since 2004 while that of dividend-paying firms continuously declined throughout the sample period. Thus, the shrunk market of the JSE does not seem to explain the drop in the number of firms paying dividends. In pursuit of specific reasons to explain the declining dividend payment trend, the study proposes five hypotheses based on the evidence from the literature. The first four predictions are based on firm-specific factors (profit, size, free cash flow and investment opportunities), while the last one is based on the propensity of firms to pay dividends over the sample period. All three methods of analysis used show either very strong or some evidence that profitability and size play a significant role in the decision of a firm to pay dividends. Although there is evidence regarding a firm’s investment opportunities, the study shows that this would be subject to a particular time frame and the size of the firm. Additionally, the fifth prediction based on the firms ‘propensity to pay dividends was supported by all three methods of analysis. Therefore, firms, in general, were less inclined to pay dividends over time during the sample period irrespective of firm-specific factors. Furthermore, the study incorporates the contribution of certain major economic and regulatory events in explaining the observed declining number of dividend-paying firms.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Johannesburg Stock Exchange (JSE); Non-financial firms; Dividends